2003
DOI: 10.1002/bit.10866
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of membrane fouling by protein mixtures using MALDI‐MS

Abstract: Binary aqueous solutions of bovine serum albumin (BSA) and beta-lactoglobulin (bLG) were subject to flux-stepping and constant flux ultrafiltration to identify the apparent critical flux and to study the mechanisms and factors affecting fouling when the membrane is permeable to one protein component. Membranes from these filtration experiments were analyzed using matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS) to locate and quantify levels of fouling below and above the apparent critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…There have been numerous studies on protein fouling of other types of membranes [8][9][10][11][12], but limited studies on fouling of RO membranes. The fouling mechanisms of MF membranes by BSA have been attributed to membrane pore blocking and/or pore constriction during initial fouling, followed by cake formation on the membrane surface during long-term fouling [12].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies on protein fouling of other types of membranes [8][9][10][11][12], but limited studies on fouling of RO membranes. The fouling mechanisms of MF membranes by BSA have been attributed to membrane pore blocking and/or pore constriction during initial fouling, followed by cake formation on the membrane surface during long-term fouling [12].…”
Section: Introductionmentioning
confidence: 99%
“…9,12 Regrettably, the high performance of UF membranes is not easily maintained over time as significant fouling occurs after the process commences. [14][15][16] Although membrane fouling is a very complicated process, many investigations have shown that an increment in membrane hydrophilicity will inevitably inhibit protein adsorption and deposition, thereby significantly reducing membrane fouling. [17][18][19] Therefore, the ionic modification was applied with the aid of dual-layer hollow fiber technology in this work to tune the pore size and pore size distribution, introduce the electrostatic interaction, and reduce membrane fouling for longterm high-performance protein separation.…”
Section: Introductionmentioning
confidence: 99%
“…Centrifugal ultrafiltration is used to for enrich low-molecular-weight proteins, which are considered as an important source of biomarkers [21, 22]. In contrast, protein precipitation is often more preferable other than ultrafiltration, because the membranes are not so robust enough for high protein concentrations and suffering from fouling that used for ultrafiltration [23, 24]. Recent reviews have systematically described the increasing number of initial fractionation approaches used for plasma proteomic analysis [25].…”
Section: Introductionmentioning
confidence: 99%